2017
DOI: 10.1097/md.0000000000006460
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of laparoscopic versus open liver resection for hepatocellular carcinoma for various resection extent

Abstract: Although the number of laparoscopic liver resections (LRRs) has increased, studies of surgical outcomes in comparison with the conventional open approach are limited. The purpose of this study was to analyze the surgical outcomes (safety and efficacy) of LLR versus open liver resection (OLR) for hepatocellular carcinoma (HCC).We collected data on all patients who received liver resection for HCC between April 2015 and September 2016 in our institution, and retrospectively investigated the demographic and perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 32 publications
0
39
2
Order By: Relevance
“…36 Either way, both CRLM and HCC represent the most amenable indications to LLR because of the earlier return to systemic therapy and parenchyma preserving benefits (possibly influencing reoperability) on one hand and because of the diminished manipulation, preservation of collaterals, and decreased decompensation and ascites production on the other hand. [37][38][39][40] Despite this, due to the increased chance of bleeding, cirrhosis is still treated with caution, as evidenced by the low percentage of cirrhotic patients in this series (Table 1). Of note, the altered liver background increases the difficulty of the procedure, increasing the probability of conversion, especially in demanding procedures, such as major hepatectomies and PS segment resections.…”
Section: Discussionmentioning
confidence: 90%
“…36 Either way, both CRLM and HCC represent the most amenable indications to LLR because of the earlier return to systemic therapy and parenchyma preserving benefits (possibly influencing reoperability) on one hand and because of the diminished manipulation, preservation of collaterals, and decreased decompensation and ascites production on the other hand. [37][38][39][40] Despite this, due to the increased chance of bleeding, cirrhosis is still treated with caution, as evidenced by the low percentage of cirrhotic patients in this series (Table 1). Of note, the altered liver background increases the difficulty of the procedure, increasing the probability of conversion, especially in demanding procedures, such as major hepatectomies and PS segment resections.…”
Section: Discussionmentioning
confidence: 90%
“…As showed in table 3, we have summarized all comparative studies of major LLR vs. major OLR [4][5][6][7][8][17][18][19][20][21][22][23]. The negative margins and oncologic integrity of the procedure should be obtained, when major laparoscopic liver resection is performed for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the data on perioperative outcomes, major LLR was associated with favorable intraoperative blood loss, total postoperative complications and postoperative hospital stay in the summarized comparative studies. However, the operation time of major LLR was significantly longer than major OLR in most of the retrospective studies [4][5][6][7][8][17][18][19]21,22]. Recently, the Japanese National Clinical Database showed that major LLR was associated with less blood loss, a lower complication rate and shorter hospital stay comparing with major OLR [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopy was associated with less blood loss, shorter hospital stay, and fewer postoperative complications 64. Multiple other groups have reported similar improvements in hospital length of stay and reduced complications 6567…”
Section: Laparoscopic Versus Open Hepatectomymentioning
confidence: 96%